Were sanctuary wells in Roman Gaul intentionally contaminated using animal carcasses (3rd–4th c. AD)? - Sébastien Lepetz; Alice Bourgois (Gallia)
This paper addresses the question of animal remains (isolated bones and complete skeletons) discovered in the fill of Roman sanctuary wells in northern France and their links with the dismantling of places of worship from the 3rd c. onwards. Several recently excavated sites (Vieil-Évreux, Mesnil-Saint-Nicaise and Ménestreau) and some comparative sites are presented. The main objective of the paper is to determine to what extent the animal remains are linked to the process of destruction and deconsecration. It demonstrates different animal deposits: those trapped naturally, those thrown away voluntarily and those from raptor pellets. For the latter, it appears that some rare habitation site species (raptors, corvids) played a particular role in the abandonment of these wells. The question of their prophylactic or magical role is also addressed. Alongside these wild species, the paper also considers the role of domestic animals (e.g., ox, pig, dog and cat) found in the assemblages. It appears that the principal objective of these deposits was to render the structure unsuitable and to prevent any subsequent use by contaminating the wells and making the water inaccessible and impure.